Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.18203/issn.2454-5929.ijohns20205060
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of the inferiorly based nasolabial flap for reconstruction in early oral cancer patients: Our experience in a tertiary cancer centre

Abstract: <p class="abstract"><strong>Background:</strong> The nasolabial flap is a simple, yet efficient method of soft tissue reconstruction with a very reliable blood supply which can be used to reconstruct soft tissue defects of various parts of the oral cavity. Aim of the study was to study the effectiveness of the inferiorly based nasolabial flaps for reconstruction in early oral cancer patients.</p><p class="abstract"><strong>Methods:</strong> 28 patients with T1 or T2 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The supply is from mainly facial and its transverse branch. The flap based inferiorly is supplied by facial artery and the one based superiorly is supplied by transverse facial artery [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The supply is from mainly facial and its transverse branch. The flap based inferiorly is supplied by facial artery and the one based superiorly is supplied by transverse facial artery [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…For limited defects following tumor resection in the buccal mucosa of floor of the mouth, nasolabial flaps show good functional and esthetic results [4,15,16]. Speech remains unaffected [12,13], there is minimal morbidity of donor site [12,13]. None of the studies reported of patient complaint regarding cosmetic appearance [9].…”
Section: Pic 3 Final Appearance After Donor Side Closurementioning
confidence: 99%
See 2 more Smart Citations